Society of obstetrics and gynecologOkapani, A.y of Nigeria – clinical practice guidelines: guidelines for the prevention of cervical cancer (2019)
Clinical practice guidelines have been developed by professional societies globally. Each guideline although based on published scientific evidence reflected each country’s socioeconomic peculiarities and unique medical environment. The Society of Obstetrics and Gynaecology of Nigerian has published guidelines in other clinical areas; however, this is the first edition of practice guidelines for the prevention of cervical cancer. The Guidelines Committee was established in 2015 and decided to develop the first edition of this guideline following Delphi pool conducted among members which selected cervical cancer prevention as the subject that guideline is urgently needed. These guidelines cover strategies for cervical cancer prevention, screening, and management of test results. The committee developed the draft guideline during a 2‑day workshop with technical input from Cochrane Nigeria and Dr. Chris Maske, Lancet Laboratories, South Africa. The recommendations for each specific area were developed by the consensus, and they are summarized here, along with the details. The objective of these practice guidelines is to establish standard policies on issues in clinical practice related to the prevention of cervical cancer.